A comparison of global coagulation assays between normal controls and patients with thrombocytopenia. (26th October 2018) - Lim, Hui Yin; Leung, Patrick; Manitta, Vanessa; Nandurkar, Harshal; Ho, Prahlad
Abstract: Introduction: Some patients with thrombocytopenia may be at risk of bleeding although quantitative platelet count is not always a sufficient predictive factor. Global coagulation assays such as thromboelastography (TEG ® ), calibrated automated thrombogram (CAT) and overall haemostatic potential (OHP) may provide a better assessment of an individual's haemostatic profile. Methods: Blood samples were collected from thrombocytopenic patients. TEG ® was performed on citrated whole blood, while CAT and OHP were performed on platelet‐poor plasma. Results were compared to our previously collected normal controls. Results: Fifty‐eight participants (24 immune thrombocytopenia, 34 chemotherapy/malignancy‐related) with mean age of 57.5 years were recruited. Compared to normal controls, thrombocytopenic participants had comparable maximum amplitude but reduced clot lysis (0.0% vs 0.6%; P  < 0.001) on TEG ® with reduced endogenous thrombin potential on CAT (1252.2 vs 1353.0 nmol/L/min; P  = 0.040). No differences were seen in the OHP parameters. TEG ® showed significant difference between marked and mild thrombocytopenia groups with minimal differences seen on CAT and OHP. Those with marked thrombocytopenia showed reduced maximum amplitude (47.2 vs 57.8 mm; P  = 0.002) as expected while participants with mild thrombocytopenia (platelet count 100‐150 × 10 9 /L) paradoxically demonstrated increased maximum amplitude (66.4 vs 57.8 mm; P  < 0.001). Conclusion: Global coagulation assays, particularly TEG ®, can detect subtle differences in coagulation in thrombocytopenic patients. While patients with marked thrombocytopenia showed reduced maximum amplitude, patients with mild thrombocytopenia appear to paradoxically show increased maximum amplitude, suggesting compensatory activity within the coagulation pathway which may in part explain why not all thrombocytopenic patients have bleeding complications.